Oil-degrading bacterial consortium from Gulf of Mexico designed by a factorial method, reveals stable population dynamics - Rojas-Vargas, Jorge; Adaya, Libertad; Silva-Jiménez, Hortencia; Licea-Navarro, Alexei Fedorovish; Sanchez-Flores, Alejandro; Gracia, Adolfo; Pardo-López, Liliana (Frontiers in Marine Science, 2022)
We describe an assembled marine bacterial consortium designed for bioremediation of oil-contaminated seawater, based on a statistical method using a Plackett-Burman (PB) experimental approach. The final consortium consists of four strains isolated from the Gulf of Mexico, from four genera: Pseudomonas, Halopseudomonas, Paenarthrobacter, and Alcanivorax. Individually, bacterial oil removal by these microorganisms was evaluated by gravimetry, reaching 39% at maximum after 75 days, whereas in consortium it was ~62%. We also measured biodegradation levels by Gas Chromatography/Mass Spectrometry (GC-MS) observing 12 polyaromatic hydrocarbons (PAHs) degradation analyzed and n-alkanes degradation with a preference for specific chain length. Consortium population analysis using the V3-V4 region of 16S rRNA showed a stable community, suggesting that the metabolic load was distributed among strains and that stable dynamic interactions were achieved. In this work, we show that the use of a factorial method for synthetic consortium design offers the possibility of improving oil degradation efficiency with stable bacterial populations.